PERAN INSTRUMEN DISTRIBUSI EKONOMI ISLAM DALAM MENCIPTAKAN KESEJAHTERAAN DI MASYARAKAT - Ghofur, Ruslan Abdul (IKONOMIKA, 2016)
Abstract- Human abstraction as the representative of God on earth that has been assigned to manage and improve the quality of life of all its inhabitants, has a great responsibility in achieving the task. But the reality, the awareness for running the obligation of zakat and create prosperity on earth only in some people.This research uses descriptive method kualitatif.Penelitian it aims to find out how much economic instruments such as the Islamic waqf, zakat donation as one of the tools mrnciptakan economic well-being of the community fair. The results of this study found that, synergies instruments such distribution zakat alms donation can be able to create a comprehensive social security for every all levels of society. In addition to the creation of prosperity will ease the burden of the government in addressing the problem of poverty and pengagangguran which has been the economic development of Indonesia homework.